2022
DOI: 10.1021/acs.analchem.1c04690
|View full text |Cite
|
Sign up to set email alerts
|

Glycan and Protein Analysis of Glycoengineered Bacterial E. coli Vaccines by MALDI-in-Source Decay FT-ICR Mass Spectrometry

Abstract: Bacterial glycoconjugate vaccines have a major role in preventing microbial infections. Immunogenic bacterial glycans, such as O-antigen polysaccharides, can be recombinantly expressed and combined with specific carrier proteins to produce effective vaccines. O-Antigen polysaccharides are typically polydisperse, and carrier proteins can have multiple glycosylation sites. Consequently, recombinant glycoconjugate vaccines have a high structural heterogeneity, making their characterization challenging. Since deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Additionally, the conjugation rate, or quantity of polysaccharides conjugated to one single carrier protein, varies as well. For these reasons, the structure elucidation of the conjugate is not evident and requires several methods [ 72 , 73 ]. Next to this, there are some other challenges, such as OTases, that are not fully compatible with most bacterial O-SP, resulting in even more heterogeneous bioconjugates.…”
Section: Conjugate Vaccine Carriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the conjugation rate, or quantity of polysaccharides conjugated to one single carrier protein, varies as well. For these reasons, the structure elucidation of the conjugate is not evident and requires several methods [ 72 , 73 ]. Next to this, there are some other challenges, such as OTases, that are not fully compatible with most bacterial O-SP, resulting in even more heterogeneous bioconjugates.…”
Section: Conjugate Vaccine Carriersmentioning
confidence: 99%
“…This new and exciting field of conjugate vaccines is already well studied ( Table 2 ). Nicolardi et al describe the development of a protein-based glycoengineered vaccine using the exotoxin A from P. aeruginosa as a carrier targeting E. coli serotypes O2, O6A and O25B [ 72 ]. Harding et al report (1) on a polyvalent pneumococcal bioconjugate vaccine using the natural acceptor protein ComP as a vaccine carrier decorated with S. pneumoniae CPSs [ 74 ] and (2) K. pneumoniae K1 and K2 serotypes produced in glycoengineered E. coli .…”
Section: Conjugate Vaccine Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…16 We and Nicolardi et al recently reported the first example of glycan-selective MALDI−ISD analysis from intact glycoprotein. 17,18 A sodium-doped super DHB (DHB/5-methoxy salicylic acid/Na) caused random ISD fragmentation of artificial N-glycans having bacterial O-antigen polysaccharide repeats to give the sequence information of the repeat units. 18 A solid salt matrix composed of aniline/DHB/Na 19 caused selective ISD at the reducing ends of N-glycans and glycan fragment selective ionization, making this top-down glycomic analysis possible.…”
Section: ■ Introductionmentioning
confidence: 99%
“…17 , 18 A sodium-doped super DHB (DHB/5-methoxy salicylic acid/Na) caused random ISD fragmentation of artificial N -glycans having bacterial O-antigen polysaccharide repeats to give the sequence information of the repeat units. 18 A solid salt matrix composed of aniline/DHB/Na 19 caused selective ISD at the reducing ends of N -glycans and glycan fragment selective ionization, making this top-down glycomic analysis possible. 17 However, the intensity of the glycan fragment ion signals obtained by MALDI–ISDMS analysis using this aniline/DHB/Na matrix was still insufficient to detect minor glycan components and to analyze glycoprotein containing biofluid.…”
Section: Introductionmentioning
confidence: 99%